2014
DOI: 10.1177/1742271x14554678
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional relationships with ultrasound measured muscle thickness of the upper extremity and trunk

Abstract: Unless a subject's muscle is relatively small, a single image from a standard ultrasound can only measure muscle thickness (MT). Thus, it is important to know whether MT is related to morphological and functional characteristics of individual muscles of the extremity and trunk. In this review, we summarize previously published articles in the upper extremity and trunk demonstrating the relationships between ultrasound-measured MT and muscle morphology (cross-sectional area, CSA and muscle volume, MV) and muscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 36 publications
5
28
2
Order By: Relevance
“…The distance between the two interfaces was measured with a ruler. The precision and linearity of the image reconstruction have been confirmed and are described elsewhere (Abe et al 2014a). Test-retest reliability of MT-ulna measurements using the intra-class correlation coefficient (ICC 3,1 ), standard error of measurement (SEM), and the minimal difference needed to be considered real (Weir 2005) was previously determined for data from 23 young and middle-aged adults (13 men and 10 women) scanned twice 24 h apart: 0.994, 0.06 cm, and 0.17 cm, respectively.…”
Section: Subjectsmentioning
confidence: 97%
“…The distance between the two interfaces was measured with a ruler. The precision and linearity of the image reconstruction have been confirmed and are described elsewhere (Abe et al 2014a). Test-retest reliability of MT-ulna measurements using the intra-class correlation coefficient (ICC 3,1 ), standard error of measurement (SEM), and the minimal difference needed to be considered real (Weir 2005) was previously determined for data from 23 young and middle-aged adults (13 men and 10 women) scanned twice 24 h apart: 0.994, 0.06 cm, and 0.17 cm, respectively.…”
Section: Subjectsmentioning
confidence: 97%
“…We recently reported the morphological and functional relationships with ultrasound measured MT of the upper extremity and trunk. 10 Thus, the purpose of this brief review was threefold. First, we discuss the validity and reliability of MT measurements in the thigh and lower leg muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound is a non-invasive, quick, and safe imaging technique that can be easily applied in clinical assessment and field survey. The precision and linearity of ultrasound image reconstruction have been confirmed (Abe et al 2014b). Thus, these newly developed equations could be a valuable tool in population-based studies to assess a criterion for defining age-related muscle loss (i.e., sarcopenia), although validation in other ethnic groups must be investigated in the future.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, a study revealed that there are strong correlations (r = 0.95-0.99) between MRI-measured whole body and regional (thigh, lower-leg, arm, and trunk) muscle mass in men and women (Abe et al 2003). The linear relationship between MT and muscle CSA or muscle volume has been observed in upper and lower extremity muscles in both sexes (Abe et al 2014b). As a result, our newly developed equations mainly included MT from the extremities, as DXA-derived aLM does not include trunk muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation